Sewage Sludge And Red Gypsum Composite Applicability As Alternative Materials For Intermediate Landfill Cover - Rosli, Nor Azalina (2021)
Application of soil as landfill cover is not economical nor environmentally sustainable; instead, soil can be more beneficial in agricultural and construction sectors. Past studies replaced soil as landfill cover with waste such as sewage sludge and fly ash, primarily for application in a temperate climate. This study attempts to apply sewage sludge (SS) and red gypsum (RG) as a composite for landfill cover, which is currently disposed of as scheduled waste in secured landfills in Malaysia. The study investigated the optimum design mix based on the characterization of hydraulic conductivity (k), unconfined compressive strength (UCS) and plasticity index (PI), as well as scrutinizing the role of SS and RG in the composite. The study also examined the effect of compaction on the characteristics of composite in terms of k, UCS and leaching behaviour. The standard deviation and error bar was reported for the measurement, and regression analysis was conducted to study the correlation between parameters using Minitab 17 software. A series of column test using the constant head method was carried out by percolating distilled water (DW) or synthetic leachate (SL) through composites compacted to 60, 70, 75, 80 and 85 % by weight. The leachate quality was monitored at pre-determined days for pH, BOD, COD, Cu, Fe and Zn. The SS:RG composite of 1:1 corresponds to Ca:Si ratio of 2.5:1 was found ideal for calcium silicate hydrate (CSH) formation, recorded a UCS of 520 kPa, k of 10-5 cm/s, and PI of 28.5 %, favourable for application as landfill cover. The plastic behaviour was attributed to the coagulating performance of iron (Fe) in RG, contributing to the micro-aggregation in the composite. The degree of compaction was linearly correlated with initial porosity but did not affect k in the case of DW. However, k changed at 75 % when SL percolated through the composite. The k decreased in three stages; the first two stages were predominated by the rearrangement of particles and hydration of CSH, followed by stabilization of k in the third stage. The faster reduction of k by about one magnitude order in the case of SL was attributed to the entrapment of heavy metal precipitated within the matrices of CSH gel. The composite did not exhibit potential environmental pollution, and compaction at 75 % reduced the strength of leachate for the receiving leachate treatment system. This study recommended a minimum of 80 % compaction for a landfill operation. These findings will be a useful reference for developing alternative composite for landfill cover in tropical climates, such as Malaysia.